Upaya Guru Al-Qur’an Hadis Dalam Meningkatkan Kemampuan Membaca Al-Qur’an Siswa di MTs Swasta Madinatussalam - Arlina; Siagian, Muhammad Aldi; Adelia, Purnama Sastra; Rangkuti, Rabiatul Adawiyah (Ikatan Dai Indonesia, 2023)
The purpose of this article is to examine the efforts of Al-Quran hadith teachers to improve Reading Comprehension of the Al-Quran by Madinat Salaam Private MT Students. The method used in this study is descriptive-qualitative using instrumental data collection techniques, interviews and triangulation followed by simple analysis. The conclusion of this study is that the Al-Qur'an as a guide for worship must be regulated properly and correctly, starting with reading it according to the correct rules, understanding it, believing in its truth and practicing its contents. In this regard, Private Al-Quran Hadith Tutor Madinathusalaam MT seeks to improve students' Al-Quran reading skills through tutorials guided by Al-Quran Hadith teachers.